The Influence of Green Products, Healthy Lifestyle, and Brand Image on Purchasing Decisions of Lemonilo Noodles in Bangkalan City – Kamal Village - Aisya Putri; Devangga Pratama; Syamsul Arifin (Penerbit Jurnal Indonesia, 2025)
This study aims to determine the influence of Green Product, Healthy Lifestyle, and Brand Image on purchasing decisions for Lemonilo instant noodles. The background of this study is based on the increasing consumer awareness of the importance of healthy and environmentally friendly products, as well as the growing image of Lemonilo as a pioneer of healthy instant noodles in Indonesia. The research method used is a quantitative approach with multiple linear regression analysis techniques. Data were obtained from 93 respondents in Kamal Village, Bangkalan Regency, collected through questionnaires. The independent variables in this study are Green Product (X1), Healthy Lifestyle (X2), and Brand Image (X3), while the dependent variable is Purchase Decision (Y). The results of the study indicate that partially and simultaneously the three independent variables have a significant effect on purchasing decisions. The regression coefficient shows that Green Product has the most dominant influence, followed by Brand Image and Healthy Lifestyle. The R Square value of 1.000 indicates that 100% of the variation in purchasing decisions can be explained by these three variables. This study concludes that environmental aspects, healthy lifestyle, and brand image are important factors in influencing consumer behavior towards purchasing Lemonilo instant noodles. This research is expected to provide input for companies in developing marketing strategies based on sustainability and health.